Archaeological Applications of Advanced Imaging Techniques - Bearman, Gregory H. (The Biblical archaeologist, 1996)
Utilizing techniques developed by NASA, the imaging of texts on papyri, parchment, pottery, or plaster can capture much information invisible to the naked eye. Multi-spectral imaging and computer manipulation of digital images enhances legibility of obscured Dead Sea Scroll texts and faded ostraca alike.